Folha de S. Paulo: a semântica global e os atos de violência nas manifestações sociais - Rodrigues, Nilson de Oliveira (2018)
This research reflects upon the global semantics on the construction of the journalistic discourse in editorials. Having as background the relation between the discourse frames, our objective is to verify how the dimensions of global semantics operate the theme of violent acts during social protests on the functional practice of journalistic discourse. This theme is relevant hence the issue of violence has increasingly become a focus of attention in our society. Based on the assumption that each discourse frame has its own relevant marks and that there is a system of global constraints that rules the discourse, we have chosen as theoretical reference the French line Discourse Analysis, more specifically the enunciative discourse device proposed by Maingueneau (2008b). We have elected as the categories of analysis the interdiscourse, the frames of global semantics – vocabulary, intertextuality, theme, enunciator and co-enunciator statute, discursive deixis, mode of enunciation mode and cohesion mode, besides the conditions of elaborating discourses. The reference corpus is constituted by three editorials on the newspaper Folha de S.Paulo, among them, two from 2013 and one from 2016, all spread right after big street protests. On the analysis, based on the principle of global semantics, we have verified that it is not feasible to privilege a frame and disregard the others, which made us realize that the effects of sense emerge not from only one, but from the whole set of frames, organized according to the global semantics. Based on the results achieved, we have also validated that the global semantics allows to deepen an apprehension of the limits of discursiveness in order to acknowledge that the system of semantic constraints sets up the principles which makes the discourse from the newspaper Folha de S.Paulo belongs to distinct positions, even when dealing with the same theme during close time periods. The paradigm of transdisciplinarity urges us to spread our view to other areas to increase our reflections: on the questions related to journalistic discourse, we were based on Kunczik (1997) and Melo (1994, 2006). For the study on media, we have applied to Charaudeau (2015); for the study on violence, we have consulted Dias (2008), Michaud (1989), among others